Hubungan Dukungan Keluarga, Peran Bidan dan Motivasi Ibu dengan Perilaku Mobilisasi Dini Pasca SC di RSIA Brawijaya Duren Tiga Jakarta Tahun 2022 - Yetti Dianca A’Yun Nadziroh; Istiana Kusumastuti; Astrid Novita (MPI Press, 2023)
Introduction: Early mobilization can maintain a person's independence to guide the patient out of bed such as walking, and moving limbs in a left and right tilt. Family support, the role of the midwife and the mother's motivation are one of the success factors in early mobilization behavior after surgery. Objectives: This study aims to determine the relationship between family support, the role of midwives and mother's motivation with early post-SC early mobilization behavior at RSIA Brawijaya Duren Tiga Jakarta in 2022. Method: This study used an analytic method with a cross-sectional approach with a total sample of 58 patients. In this study, the instrument used was a questionnaire with data analysis using the Chi-Square test. Result: The results of this study indicate that there is a relationship between family support and early mobilization behavior, obtained a P-Value of 0.002 and OR = 1.029 (0.294-3.604), the relationship between the midwife's role and early mobilization behavior with a P-Value of 0.029 and OR = 0.900 (0.267-3.029), and the relationship between maternal motivation and early mobilization behavior obtained P-Value 0.022 and OR = 1.095 (0.329-3.648). Conclusion: There is a relationship between family support, the role of midwives and the mother's motivation with early post-SC mobilization behavior at RSIA Brawijaya Duren Tiga Jakarta in 2022.